Eat, sleep, repeat: The role of the circadian system in balancing sleep-wake control with metabolic need - Northeast, RC; Vyazovskiy, VV; Bechtold, DA (Elsevier, 2020)
Feeding and sleep are behaviours fundamental to survival, and as such are subject to powerful homeostatic control. Of course, these are mutually exclusive behaviours, and therefore require coordinated temporal organisation to ensure that both energy demands and sleep need are met. Under optimal conditions, foraging/feeding and sleep can be simply partitioned to appropriate phases of the circadian cycle so that they are in suitable alignment with the external environment. However, under conditions of negative energy balance, increased foraging activity must be balanced against sleep requirements and energy conservation. In mammals and many other species, neural circuits that regulate sleep and energy balance are intimately and reciprocally linked. Here, we examine this circuitry, discuss how homeostatic regulation and temporal patterning of sleep are modulated by altered food availability, and describe the role of circadian system in adaptation to metabolic stress.